157k views
11 votes
Solve and check
y = 3x - 10
y = 2x - 5

User Dropout
by
5.4k points

2 Answers

13 votes

Answer:

x = 5, y = 5

or

(5, 5)

Explanation:

they both equal y so they also equal each other.

3x - 10 = 2x - 5

3x - 2x = -5 + 10

x = 5

substitute x for 5

y = 3x - 10

y = 15 - 10

y = 5

edit, whops forgot to check

just plug the variables in with their values and see if it makes sense:

y = 2x - 5

5 = 2*5 - 5

5 = 10 - 5

5 = 5

since 5 does equal 5, the solution is correct.

User Abeba
by
6.0k points
8 votes

Answer:

This is the subtraction method

Y -3X = -10

(-Y -2x = -5) -Y + 2X = 5

Y -3X = -10

-Y + 2X = 5

-X = -5

X = 5 Now fill in the 5 for X and Y = 5

User Ping
by
4.9k points